The Effect Of Entrepreneurship Competence And Islamic Business Ethics On The Performance Of Micro And Small Enterprises (SMEs) Makassar - Soumena, Fadly Yashari (ITB AAS INDONESIA Surakarta, 2024)
The objective of this study is to (1) investigate the effect of entrepreneurial skills on the performance of micro and small enterprises (MSEs) in Makassar, (2) explore the implications of Islamic business ethics on the performance of MSEs in Makassar. The primary data were collected using questionnaires and multiple regression analysis. The population of this study were all participants of MSEs in Pasar Cidu, Makassar, and the sample used in this study consisted of 40 representatives, and the data obtained were analyzed by IBM SPSS Statistics 26. The results of this study indicate that (1) several business skills have a significant influence on the performance of SMEs, (2) some Islamic business ethics have a significant influence, and (3) both variables concurrently have a significant impact on the performance of SMEs in small and medium enterprises. So far, research findings suggest that entrepreneurial competence and Islamic business ethics strongly influence the performance of SMEs in Makassar. The significance of this study is to show that entrepreneurial ability has a substantial impact on the performance of SME participants. Likewise, Islamic business ethics influence consumers in making a purchase decision.